The Meaning of Support: A Husband Perspective of Women Cancer Survivor - Fitriani Nissa Rahayu; Martyarini Budi Setyawati; Adiratna Sekar Siwi; Made Suandika (Universitas Muhammadiyah Surakarta, 2022)
Women's long journey as cancer survivors makes them need husband's support. However, it was found that the wife felt the support received was less effective and the husband did not fulfill his wishes, even though the husband considered the support provided to be adapted to his wife's needs. So there is a difference in understanding related to the support given by the husband with the support received by the wife. This study aims to determine the definition of husband's support for his wife as a cancer survivor from the husband's perspective. This study uses a qualitative method with a phenomenological approach. The samples obtained were 7 people. Data collection techniques using interviews and field notes. The data analysis used is the Miles and Huberman model. The results of the study found 3 themes, namely the definition of husband's support, the reason for the husband to provide support and the form of support. 6 participants know the definition of husband's support and the rest do not know. There is one reason the husband provides support. The form of support provided by the husband is instrumental, informative, emotional, appreciation, monitoring, prioritizing and trusting the wife. Each husband has a different perspective both in defining support, reasons for giving support and efforts to support his wife. Nurses and wives are expected to understand each other's perspectives because the differences that occur cannot be generalized.